The winner is... - Harper, Charise Mericle (Next best junior chef, 2019)
Two talented junior chefs have sliced and diced their way into the finale of Next Best Junior Chef. This week's theme: innovation. Which junior chef will rise to the top and earn the title of Next Best Junior Chef? And whose goose is cooked? Two contestants compete on- and off-camera, but only one will win the whole enchilada. This is a finale you won't want to miss!